ARMS-NF-?B signaling regulates intracellular ROS to induce autophagy-associated cell death upon oxidative stress. - Liao, Y.H.; Wu, J.T.; Hsieh, I.C.; Lee, H.H.; Huang, P.H. (iScience, 2023)
Ankyrin repeat-rich membrane spanning (ARMS) plays roles in neural development, neuropathies, and tumor formation. Such pleiotropic function of ARMS is often attributed to diverse ARMS-interacting molecules in different cell context. However, it might be achieved by ARMS' effect on global biological mediator like reactive oxygen species (ROS). We established ARMS-knockdown in melanoma cells (siARMS) and in Drosophila eyes (GMR>dARMS [RNAi]) and challenged them with H2O2. Decreased ARMS in both systems compromises nuclear translocation of NF-?B and induces ROS, which in turn augments autophagy flux and confers susceptibility to H2O2-triggered autophagic cell death. Resuming NF-?B activity or reducing ROS by antioxidants in siARMS cells and GMR>dARMS [RNAi] fly decreases intracellular peroxides level concurrent with reduced autophagy and attenuated cell death. Conversely, blocking NF-?B activity in wild-type flies/melanoma enhances ROS and induces autophagy with cell death. We thus uncover intracellular ROS modulated by ARMS-NF?B signaling primes autophagy for autophagic cell death upon oxidative stress.